A Physical Map of the Leishmania majorFriedlin Genome - Ivens, Alasdair C.; Lewis, Sharon M.; Bagherzadeh, Azadeh; Zhang, Linglan; Chan, Ho M.; Smith, Deborah F.

(untitled) (Genome Research, 1998)
An extensive physical map of the Leishmania majorFriedlin genome has been assembled by the combination of fingerprint analysis of a shuttle vector cosmid library and probe hybridization. The integrated data obtained for 9004 fingerprinted clones and 974 probes have placed 91.2% of the 33.58-Mb genome into contigs representing each of the 36 chromosomes. This first-generation map has already provided a suitable framework for both high-throughput DNA sequencing and functional studies of the L. major parasite.